Durability of resin-zirconia bonds produced using methods available in dental practice - Bömicke, Wolfgang; Schürz, Alexander; Krisam, Johannes; Rammelsberg, Peter; Rues, Stefan (The journal of adhesive dentistry, 2016)
Purpose: To evaluate the strength, after artificial aging, of resin-zirconia bonds yielded by methods available in dental practice. Materials and Methods: Standardized test specimens consisting of composite resin cylinders cemented to Y-TZP disks were assigned to 24 groups (n = 20 per group) on the basis of the surface conditioning of the disks and the adhesive used (cement + manufacturer-specific primer). Conditioning methods were: none (control), airborne particle abrasion (50-μm Al2O3 at 0.05, 0.10, or 0.25 MPa), or tribochemical silica coating (Rocatec or CoJet). Panavia 21 + Clearfil Ceramic Primer, Multilink Automix + Monobond Plus, BiFix QM + Ceramic bond, or RelyX Ultimate + Scotchbond Universal were used for cementation. Specimens were stored in water at 37°C either for 3 days or for 150 days in conjunction with 37,500 thermocycles before being submitted to a tensile test (crosshead speed: 1 mm/min). Nonparametric ANOVA and post-hoc tests within the same model were applied to the results (α = 0.05). - Results: Conditioning, cement, aging, and all their interactions significantly affected bond strength (p < 0.0001). After storage in water for 3 days, bond strengths ranged between 4 and 45 MPa (values were lowest in the BiFix QM groups). After long-term aging, the best results were obtained for silica-coated (Rocatec) zirconia samples cemented with Panavia 21/Clearfil Ceramic Primer; this was the only group for which bond strengths were > 10 MPa. Premature failure of the resin-ceramic bond was usually observed during long-term aging, the only exception being the non-control groups cemented with Panavia. - Conclusion: Most bonding strategies failed to create bonds to zirconia with acceptable strength after long-term aging. It might therefore be unwise to rely solely on adhesion for retention of load-bearing Y-TZP restorations.